Neonatal factors related to center variation in the incidence of late-onset circulatory collapse in extremely preterm infants. - Yume Suzuki; Yumi Kono; Takahiro Hayakawa; Hironori Shimozawa; Miyuki Matano; Yukari Yada; Neonatal Research Network Japan (PLoS ONE)
Background Although late-onset circulatory collapse (LCC) is widely recognized in Japan, its etiology and the reason for center variation in its incidence remain unclear. This study's objectives were to identify the perinatal and neonatal factors related to LCC and to estimate the factors related to the center variation in the incidence of LCC. Methods Extremely preterm infants born between 2008 and 2012 who were registered in the database of the Neonatal Research Network, Japan were retrospectively analyzed. LCC was defined as a clinical diagnosis of LCC and the administration of steroids. We first identified the factors that were significantly related to LCC. We then examined the cause of the center variation in the incidence of LCC, using the standardized incidence ratios (SIRs) of LCC and individual factors. Results The factors significantly associated with LCC included low gestational age (odds ratio [OR]: 1.13), small for date (OR: 1.43), male sex (OR: 1.26), antenatal steroid use (OR: 1.19), respiratory distress syndrome (OR: 1.25), chronic lung disease at 36 weeks (OR: 1.16), periventricular leukomalacia (PVL) (OR: 2.57), necrotizing enterocolitis (OR: 0.59), retinopathy of prematurity (ROP) (OR: 1.73), high-frequency oscillating ventilation (HFOV) use (OR: 1.31), parenteral nutrition (OR: 1.38), and red blood cell (RBC) transfusion (OR: 1.94). The SIR of LCC ranged from 0.05 to 2.94, and was positively correlated with SIRs of PVL, ROP, HFOV use and RBC transfusion. Conclusion PVL, ROP, HFOV use and RBC transfusion were found to be correlated with the center variation in the incidence of LCC.